Analisa Tindak Tutur Ilokusi Dalam Pertunjukan Stand-Up Komedi Trevor Noah Yang Berjudul 'Afraid of the Dark' - Houtandi, Cecillia Noveline; Adrallisman (e-LinguaTera, 2024)
Humor contains various components that lend itself to the study of language. This study focuses on the usage of illocutionary speech acts in Trevor Noah's "Afraid of the Dark" stand-up comedy show in 2017. In order attract audiences, this study aims to investigate the types and functions of speech acts. The writer discovered that Noah's usage of Searle's five illocutionary speech acts may improve the material and humor he would present. Assertive speech acts are the ones most used by Noah. The writer found 9 functions of assertive speech acts in the show. The used of illocutionary speech acts on the subject that Noah has presented can help many people broaden their perspectives.